African counternarratives: Action research in response to the construction of hegemonic stigmas - De Almeida, Elizângela Áreas Ferreira [UNESP]; Saravali, Eliane Giachetto (Universidade Estadual de Ponta Grossa (UEPG), 2022)
This article presents part of the results of action research developed in Portuguese Language classes whose main objective was to promote knowledge and reflection on the African cultural universe presented in African and Afro-Brazilian literary works. Twenty-eight students from the 8th grade of Elementary School from a state public school in the state of São Paulo, Brazil, participated of an intervention that, during the diagnostic phase, presented concepts based on prejudice and subjugation of ethnic-racial issues related to the understanding of African and Afro-Brazilian culture. In the action-reflection phase, Literary Rounds were organized, and the teenagers were able to learn and debate about different aspects of the African culture, through different textual genres. In the evaluation phase, the narratives and counternarratives elaborated by the participants of this research indicated how they appropriated and came to understand the existing ethnic-racial diversity in an increasingly miscegenated and plural country.
Contra-narrativas africanas: una investigación-acción en respuesta a la construcción de estigmas hegemónicos
Contranarrativas Africanas: uma pesquisa-ação em resposta à construção de estigmas hegemônicos
Keywords: Action-research; Afro-Brazilian counternarratives; Ethnic-racial notions